Model predictive control of heat pump water heater-instantaneous shower powered with integrated renewable-grid energy systems. (15th October 2017) - Wanjiru, Evan M.; Sichilalu, Sam M.; Xia, Xiaohua
Highlights: Robust model predictive control (MPC) strategy used to control hot water devices. Integrated renewable energy sources supplemented by grid used to power the devices. Heat pump water heater coupled with instantaneous shower is modelled. Potential daily energy and water saving of 32.24% and 19 l respectively. The proposed control strategy is suitable for peri-urban and rural home owners. Abstract: Energy and water are two inseparable resources that are crucial for human survival, yet, most developing nations are struggling to reliably provide them to the population especially in rapidly growing urban areas. Increasing demand is forcing governments, organizations and private sectors to encourage end-users to increase efficiency and conservation measures for these resources. Water heating is one of the largest energy users in residential buildings thus has a huge potential to improve the efficiency of both energy and water. In this regard, heat pump water heaters (HPWHs) have been found to improve energy efficiency while providing domestic hot water. However, impediments such as optimal operation, integration and high initial cost especially in developing nations hinder their uptake. Further, since they are normally centrally located in a house, there are water and associated energy losses during hot water conveyance to the end-use, as the once hot water in the pipes that cooled off has to be poured away while end-user awaits for hot water. Therefore, this paper advances the previously developed open loop optimal control model by using the closed-loop model predictive control (MPC) to operate a HPWH and instantaneous shower powered using integrated renewable energy systems. This control strategy has the benefit of robustly and reliably dealing with disturbances that are present in the system as well as turnpike phenomenon. It has the potential to save 32.24 % and 19 l of energy and water in a day respectively, while also promising lower energy and water bills to the end users. In addition, there is revenue benefit through the sale of excess renewable energy back to the grid through an appropriate feed-in tariff. Life cycle cost (LCC) analysis is conducted to determine the total cost of setting up and operating the system over its life, which shows that the benefits would pay back the cost of the system even before half of its life elapses. This control strategy of both hot water devices powered using integrated renewable systems is suitable for peri-urban home owners.